Implications of Independet Learning Policy on PAI Learning Evaluation Design - Eva Sari Wati Tampubolon selma; Siti Kumala; Abdul Bashith (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
This study aims to analyze the implementation of the Independent Learning Curriculum Policy in Islamic Religious Education (PAI) learning and its impact on the design of learning evaluations. The results of the study indicate that the Independent Learning Curriculum brings significant changes in the evaluation of PAI learning, with a focus on student mastery of competencies, not just memorization. The evaluations implemented include formative, summative, performance, and portfolio, which focus on understanding Islamic teachings in everyday life. In addition, this policy supports the use of technology in the evaluation process, making it easier for teachers to provide constructive feedback. However, the main challenges in its implementation are the inequality of resources and teacher readiness. In conclusion, although this policy has great potential to improve the quality of PAI learning, the success of its implementation is highly dependent on the support of more intensive training and coaching for teachers and the provision of adequate facilities.